Teachers' experiences of stress and their coping strategies during COVID-19 induced distance teaching - Florian Klapproth; Lisa Federkeil; Franziska Heinschke; Tanja Jungmann (Journal of Pedagogical Research, 2020)
Mastering distance teaching imposed by the COVID-19 pandemic was challenging for many teachers. In the present cross-sectional survey, we assessed the level of stress that teachers experienced during the lockdown of schools in Germany, their strategies to cope with it, and external and internal barriers for distance teaching with an online questionnaire. Teachers were recruited for the study on the basis of nationwide professional networks (e.g. Eduserver - Education in Germany, The German Education Union (GEW)) as well as by advertising the study on homepages of associations for different special educational needs and in social networks (e.g. Facebook, Instagram). A total of 380 teachers from different school forms participated. They experienced medium to high levels of stress. More than 50 percent of them spent more than four hours daily on remote teaching, with secondary grammar school teachers experiencing significantly more stress and working more hours daily than special education teachers. The vast majority of them experienced technical barriers, but most of them felt able to cope functionally with the stress. Female teachers experienced significantly more stress, but coped with it more often in a functional way; teachers used more functional coping strategies when they expected external factors as barriers for distance teaching. The results imply that teachers' digital skills should be developed, schools should be better equipped with the necessary computer hard- and software, and more research on psychological factors contributing to teachers' willingness to use technologies for remote teaching in the pandemic and beyond should be done.